Post orthodontic treatment stability measurement in dentoskeletal class I malocclusion based on the objective grading system index - Pasaribu, Bernard Anthony; Thahar, Bergman; Salim, Jono; Mardiati, Endah (Padjadjaran Journal of Dentistry, 2011)
The purpose of this study was to examine the stability of orthodontic treatment results in dentoskeletal class I malocclusion treated with and without extraction of four premolars and to compare the stability of treatment result between those groups. Occlusal relationship after treatment and six-month post retention were measured on dental cast using The Objective Grading System Index at Orthodontic Specialist Clinic, Faculty of Dentistry Universitas Padjadjaran. The analytic descriptive study was carried out on 30 samples that comprised 14 samples were treated without extraction of four premolars and 16 samples were treated with extraction of four premolars. ABO Measuring Gauge was used to measure seven variables: tooth alignment, the height of the marginal ridges, buccolingual inclination, occlusal relationships, occlusal contacts, overjet, and interproximal tooth contacts. The results were statistically analyzed with the Wilcoxon rank test to test the difference of The Objective Grading System Index between posttreatment and postretension. Mann-Whitney U test was applied to determine the difference between the group with the extraction of four premolars and the group without extraction of four premolars. The level of significance was set at 0.05. The results of this study showed these following variables: tooth alignment, occlusal contacts, and overjet were unstable at the group with the extraction of four premolars, while only tooth alignment was found to be unstable in the group without extraction of the four premolars. Mann-Whitney U test did not show statistically significant difference in stability comparison test between the groups.